Networked learning across contexts: University and Society collaboration for supporting sustainability and students’ future work - Reis-Andersson, Jussara; Jaldemark, Jimmy; Håkansson Lindqvist, Marcia (Proceedings of the International Conference on Networked Learning, 2026)
Rapid societal changes, particularly those driven by digital technologies and AI, necessitate innovative solutions. Academia and society, therefore, share the responsibility of equipping students with the entrepreneurial and innovative skills essential for achieving a sustainable future. Developing such competencies requires diverse and flexible approaches. One promising pathway is interdisciplinary education, which integrates knowledge and skills from multiple subjects, enabling students to connect theory with practice for holistic understanding and real-world problem-solving. Students’ prior knowledge and experiences are central to this process. Shaped by context, social interactions, and cultural elements, students’ prior knowledge and experiences influence both opportunities for learning and motivation. Creating spaces that value collaboration across disciplinary, cultural, and institutional boundaries is therefore crucial. This study investigates how students perceive learning activities designed to develop entrepreneurial and innovative skills, with a particular focus on collaborations between academia and society. The paper explores how students perceive the effectiveness of such activities and in what ways collaborations across contexts affect students’ motivation, future outlook, and readiness for work. The research draws on the BRiliant Innovation through DiGital Engagement (BRIDGE) project, in which three universities collaborated with strategic partners to design Digital Impact Day (DID) events. These events represent non-formal contexts for learning where students, university staff, and companies come together in networked educational settings to address authentic societal and organisational challenges. Findings show that DID events created a welcoming and stimulating space that encouraged engagement and collaboration. Although students faced challenges in working with unfamiliar peers, communicating across diverse backgrounds, and solving problems outside their expertise, they interpreted these difficulties as opportunities for learning, growth, and reflection. Students reported gaining confidence in teamwork, pitching, and problem-solving, as well as expanding their global perspectives on sustainability. Many students also expressed a stronger sense of preparedness for future careers and a commitment to taking meaningful action in their communities. This paper contributes to discussions on the future of teaching and learning by demonstrating how interdisciplinary and networked approaches can foster entrepreneurial and innovative skills across formal, non-formal, and informal contexts. It highlights the potential of DID events as a model for collaboration, preparing students for the complexities of future work and their role in contributing to society.